Problem-based learning in basic mathematics modules: Effects on computational thinking and resilience - Fitry Wahyuni; Reny Khaerany Nisfiary; Muhammad Daut Siagian; Ade Evi Fatimah (Universitas Hamzanwadi, 2026)
The simultaneous development of computational thinking skills and mathematical resilience remains a challenge in basic mathematics learning in higher education, primarily due to the limited number of interventions that empirically examine the relationship between the two after learning. This study aims to analyze the effect of a project-based learning (PBL)-based basic mathematics module on students’ computational thinking skills and mathematical resilience, as well as the relationship between the two constructs after the intervention. This study employed a quasi-experimental method with a single-group pretest-posttest design involving 31 students. Data were collected through a computational thinking test and a mathematical resilience questionnaire and then analyzed using descriptive statistics, normality tests, paired t-tests, effect sizes, and Pearson correlations. The results demonstrated a significant increase in computational thinking skills (t(30) = −13.348, p < 0.001, d = 2.397) and mathematical resilience (t(30) = −13.338, p < 0.001, d = 2.396), but no significant relationship was found between the two (r = 0.053, p = 0.777). These findings indicate that the PBL module is effective in improving both abilities separately, suggesting that a more integrative learning design is necessary to connect the development of both simultaneously.